Efficacy and Safety Outcomes of Intravitreal Dexamethasone Implant Therapy for the Treatment of Adult Coats’ Disease - Qingshan Chen; Saying Liang; Xizhen Wang; Chenli Hu; Jieting She; Zi Li (Journal of Ophthalmology)
Purpose. To evaluate the efficacy and safety outcomes of dexamethasone intravitreal implant in patients with Stage 3A Coats’ disease. Methods. A consecutive case series of adult Coats’ disease managed with or without intravitreal dexamethasone implant (Ozurdex®, Allergan Inc., Irvine, California, USA) injection was retrospectively evaluated. The medical records of all included patients with a minimum follow-up of 6 months were reviewed. The patients were divided into two groups according to the application of dexamethasone implant as a DEX (+) group and DEX (−) group. Laser photocoagulation, anti-VEGF agents, and vitrectomy were performed if necessary. The primary outcomes included best-corrected visual acuity (BCVA), central retinal thickness (CRT), and intraocular pressure (IOP) at month 6. Resolution of the exudative retinal detachment (ERD), subretinal fluid (SRF), and vitreous hemorrhage (VH) was also collected. Results. Ten eyes (10 patients) with Stage 3A Coats’ disease were included, and the mean follow-up time was 9.70 ± 4.42 months. The mean age was 44.20 ± 7.42 years, and 80% were male. Six eyes (6 patients) received intravitreal injection of Ozurdex were included in the DEX (+) group, while the other 4 eyes in the DEX (−) group. No significant difference of baseline characteristics including BCVA, CRT, IOP, and follow-up time can be defined between DEX (+) and DEX (−) groups. For the patients in the DEX (+) group, a significant improvement of BCVA was observed from the baseline of 1.28 ± 0.58 to 0.84 ± 0.66 logMAR at month 6 (P=0.03), while the CRT decreased from 970.33 ± 696.49 to 421.00 ± 275.76 μm (P=0.067). For the DEX(−) group, BCVA changed from 0.76 ± 0.74 to 0.96 ± 0.60 logMAR at month 6 (P=0.066), while the CRT from 382.75 ± 17.68 to 412.75 ± 195.53 μm (P=0.525) with no significant difference. IOP was elevated from 13.15 ± 1.74 mmHg at baseline to 18.05 ± 3.57 mmHg at month 6 with a P value of 0.02 for the DEX(+) group and from 14.48 ± 1.70 to 18.83 ± 4.06 mmHg (P=0.076) for the DEX (−) group. After a mean follow-up of 9.70 months, 5/6 (83.3%) eyes in the DEX (+) group and ¼ (25%) eye in the DEX (−) group achieved reattachment of ERD. Conclusion. Intravitreal dexamethasone implant therapy is effective for adult Stage 3A Coats’ disease, which provides a new treatment option for ophthalmologists.